Intramural Aortic Course Should Always Be Considered for Anomalous Origin of the Left Coronary Artery From the Right Pulmonary Artery. Issue 4 (July 2019) - Agrawal, Vishal; Vaidhya, Nikunj; Patel, Mrinal; Mishra, Amit; Patel, Dinesh
Anomalous origin of the left coronary artery (LCA) from the right pulmonary artery (ALCARPA) is an extremely rare subset of an already rare entity, anomalous origin of the LCA from the pulmonary artery. Whenever it is diagnosed preoperatively, one should be extremely vigilant about the potential intramural course of the descending part of the LCA in the aorta. Preoperative imaging frequently fails to delineate this intramural course. We report our experience with one such case where we had accidentally injured the LCA during dissection from the right pulmonary artery. Although it was successfully managed, it reinforces our aforementioned point concerning the importance of vigilance in seeking to identify intramurality as a component of this anomaly of coronary artery origin.